(untitled) (Comprehensive Journal of Science, 2026)
This study examines the complex factors contributing to security instability in Arab countries, including regional and international interventions, traditional and non-traditional threats, and cybersecurity and economic challenges. Using a descriptive-analytical approach, data is collected through a literature review, analysis of official documents and reports issued by international and regional organizations, and a review of press releases. The study relies on historical and comparative analysis to determine the evolution of security threats in the region, focusing on the most affected countries such as Syria, Yemen, and Libya. The study’s findings indicate that traditional security threats such as regional conflicts and foreign military interventions remain prevalent, while non-traditional challenges such as terrorism and extremist groups have exacerbated the security situation. The study also demonstrates the role of regional alliances in addressing some crises, although these alliances suffer from divergent internal positions among Arab countries. The study also highlights the impact of external interventions and economic crises on increasing security tensions. The study recommends the need to strengthen regional cooperation among Arab countries through organizations such as the League of Arab States and the Gulf Cooperation Council. It also recommends improving cybersecurity through strategic planning and training technical personnel. It also recommends enhancing economic stability by reducing unemployment and improving living standards, which will contribute to mitigating security tensions. The study also calls for deepening cooperation with major powers such as the United States and Russia, promoting good governance within Arab countries to reduce internal tensions, and addressing humanitarian emergencies and supporting initiatives aimed at combating terrorism.